Competence assessment in nursing education during field practices - Luis Fernando Gualdezi; Louise Aracema Scussiato; Aida Maris Peres; Thays Floris Rosa; Ingrid Margareth Voth Lowen; Danelia Gomez Torres (Universidade Federal de Santa Maria, 2020)
Objective: to analyze the knowledge of nursing students about the competences assessed during practical field classes during the training of nurses. Method: quantitative and exploratory study, with simple and descriptive statistical analysis, performed in a higher education institution in the city of Curitiba, Brazil. Data collection occurred in August 2018, with 113 nursing students through questionnaires with open and closed questions, applied during the period of classes. Results: the health care competence was highlighted as the most relevant indicated by students, followed by the skills related to health care as one of the points to be assessed during field practices; leadership did not achieve any place on the relevance scale of the assessed competences. Conclusion: the competences cited by the Brazilian National Curriculum Guidelines are assessed during the entire training process and other findings in this study make it necessary to develop more appropriate situational strategies during academic training.